Dating minerals by ID-TIMS geochronology at times of in situ analysis: selected case studies from the CPGeo-IGc-USP laboratory - Passarelli,Cláudia R. (2009)
Since 1964, the Center for Geochronological Research - CPGeo, one of the interdepartmental centers of the Instituto de Geociências (IG) of São Paulo University, has developed studies related to several geological processes associated with different rock types. Thermal Ionization Mass Spectrometry Isotopic Dilution (ID-TIMS) has been the technique widely used in the CPGeo U-Pb Laboratory. It provides reliable and accurate results in age determination of superposed events. However, the open-system behavior such as Pb-loss, the inheritance problem and metamictization processes allow and impel us to a much richer understanding of the power and limitations of U-Pb geochronology and thermochronology. In this article, we present the current methodology used at the CPGeo-IGc-USP U-Pb laboratory, the improvements on ID-TIMS method, and report high-precision U-Pb data from zircon, monazite, epidote, titanite, baddeleyite and rutile from different rock types of several domains of the Brazilian south-southeast area, Argentina and Uruguay.